The Analysis of Pollutant Parameters in Tofu Wastewater after being Treated by Contact Glow Discharge Electrolysis - Widya Pangestika; Nelson Saksono (JURNAL INTEGRASI PROSES, 2020)
Background and Objective: There are many Small, Micro and Medium Enterprises engaged in tofu processing in Indonesia. Some of them still dumped their waste directly into the river, causing the river to become turbid, had bad odor, and many aquatic organisms in the water died. Tofu wastewater contained high pollutant parameters, such as: COD, BOD, TOC, and TSS therefore, we need an effective wastewater treatment that could reduce the level of these parameters to below the standards set by the government. Materials and Methods: We used Contact Glow Discharge Electrolysis (CGDE) to treat the wastewater. Besides these four parameters, we also measured pH solution at several CGDE process voltage variations and analyzed the content of compounds contained in the initial tofu wastewater and the waste that had been treated by using CGDE. Results: From this study, we knew that the higher the voltage we used, the more acidic the solution would become. In the same operating condition, the percentage of TOC degradation was lower than the percentage of COD degradation. Voltage of 750 V gave the lowest COD and TOC values, respectively 446.6 mg/L and 320 mg/L. In addition, the best voltage that could reduce BOD and TSS degradation by 37% and by 80.2% respectively, was 650 V. Conclusion: CGDE process was able to degrade complex compounds in tofu wastewater into compounds with simpler molecular structures, such as Tris (2,4-di-tert-butylphenyl) phosphate and eicosane.